Problematika Guru dalam Penerapan Media Pembelajaran Inovatif pada Pembelajaran Seni Budaya dan Prakarya - Renzy Ayu Rohmatillah (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The role of learning media is very important in order to maximize the delivery of learning material to students. Learning media that are interesting and in accordance with learning materials will be able to attract student learning interest and knowledge can be conveyed better. This research was conducted to explore the use of innovative learning media in learning arts and culture and skills in SDN 1 Jatiprahu. The method that applied is qualitative research method and use case study approach. According to the research results from interviews and observations, it was found that there were several teacher problems in implementing innovative learning media in schools, namely the media applied to project-based learning models were still not diverse, teachers had difficulties in preparing learning media, facilities at schools were inadequate still minimal, and the government does not support learning innovations in schools.